Analysis of the Implementation of the Chronic Disease Management Program (Prolanis) in Diabetes Mellitus Patients Participants of BPJS at the Rejosari Health Center Pekanbaru City: Analisis Pelaksanaan Program Pengelolaan Penyakit Kronis (Prolanis) Pada Pasien Diabetes Melitus Peserta BPJS Kesehatan Di Puskesmas Rejosari Kota Pekanbaru - Nurul Latifah; Ahmad Hanafi; Zainal Abidin; Dami Yanthi; Yanwir Kamal (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Chronic Disease Management Program (Prolanis) is a health program that aims to prevent chronic disease complications from BPJS Health, this program can facilitate routine health checks for people with chronic diseases. The chronic diseases that Prolanis focuses on are Diabetes Mellitus and Hypertension. Based on data from the Pekanbaru City Health Office in 2020, it is known that the Rejosari Health Center has the highest number of Diabetes Mellitus patient visits in the city of Pekanbaru as many as 1,757 patients. This study aims to determine how the implementation of the Chronic Disease Management Program (Prolanis) in Diabetes Mellitus Patients participating in BPJS Health at the Rejosari Health Center Pekanbaru City in 2022. The type of research carried out was qualitative with a phenomenological design. The data collection method was carried out by observation and in-depth interviews with 6 informants, namely the head of the puskesmas, the person in charge of the program, the implementing officer, and 3 prolanis participants with diabetes mellitus. The results of this study indicate that the implementation of prolanis at the Rejosari Health Center has not been effective because there are still many obstacles and obstacles that exist in the Rejosari Health Center. It can be concluded that the implementation of prolanis is still not optimal, due to the shortage of prolanis officers and the overlapping of tasks in the puskesmas making several prolanis activities constrained, only 3 out of 5 prolanis activities are carried out at the Rejosari health center in Pekanbaru city. It is recommended to the Rejosari Health Center to add officers for the implementation of prolanis so that all prolanis activities can be carried out.